Perkembangan Tingkat Pengembalian Investasi Pendidikan Antar-Provinsi: Indonesia Family Life Survey 1993–2014 - Hendajany, Nenny; Widodo, Tri; Sulistyaningrum, Eny (Jurnal Ekonomi dan Pembangunan Indonesia, 2016)
This study traces the evolution of return to education using large samples from Indonesia Family Life Survey (IFLS). This study apply Mincer Model to find rate of return to education. The rate of return to education decrease from 1993 to 2014 in Indonesia. Interestingly, the declining rate for return to education for men is much larger than for women. Return to education is considerably heterogenic across province and gender. Furthermore, the rate of women is larger than men. Finally, this study find potential experience have not different from 1993 to 1997, but have increased in 2000 and 2014.